INTERNAL AUDITING. - Fernald, Henry B. (The Accounting Review, 1943)
The subject of internal auditing is receiving increasing attention because of the recognition given by accounting authorities and governmental regulations to its importance in determining the scope of audit necessary as a basis for an independent accountant's certificate. Sometimes people are inclined to think of accounting and auditing standards as those of large business concerns and forget that the majority of business organizations are relatively small. Most public accounting work is with relatively small business concerns. It is well to look at the highest possible accounting standards that can be developed and what can be done where cost is not a major controlling factor. Yet one must remember that small business enterprises still exist and furnish a problem of what can be done best to meet their needs. Hence one need to consider internal audit and control in the small as well as in the large business. Manifestly, if the independent auditors, in making their examination and tests, find that every feature of the accounting has been subject to a careful and adequate internal audit, the auditors can place much reliance on the internal auditing and correspondingly shorten their own work.